Comparison of complete vs. culprit-only revascularization in acute myocardial infarction - Ran Chen; Jingping Lu (BMC Cardiovascular Disorders)
Abstract Background The diagnosis and treatment of acute myocardial infarction (AMI) complicated with multivessel disease (MVD) by percutaneous coronary intervention (PCI) has been well recognized. However, the use of PCI in non–infarct-related coronary arteries remains controversial. We aimed to study the clinical outcome of complete vs. culprit-only revascularization for AMI with MVD before discharge. Methods 173 AMI with MVD who received emergent PCI between January 2013 and December 2018 were retrospectively analyzed. Patients were divided into complete revascularization (CR) group (n = 85) and culprit-only revascularization (COR) group (n = 88). Major adverse cardiovascular and cerebral events (MACCE) at 1, 6, and 12 months after PCI were compared, including recurrent angina, recurrent MI, in-stent thrombosis, new-onset atrial fibrillation (AF), and worsen heart failure (HF). Results Baseline characteristics of two groups were comparable. There was no significantly statistical difference in MACCE between COR group and CR group, 36.2% vs. 33.3% (P = 0.715), 42.0% vs. 29.7% (p = 0.125) and 44.9% vs. 36.5% (p = 0.304) at 1-, 6- and 12-month follow up respectively. Compared with the CR group, a higher rate of recurrent angina was in COR group (20.3% vs. 5.4%, P = 0.007) at the 6th month. Subgroup analysis showed that hypertensive patients benefited more from complete revascularization at the 6- (OR:0.31, 95%CI: 0.13–0.76) and 12-month (OR:0.38, 95%CI: 0.16–0.90) follow up. Conclusions Complete revascularization before discharge does not supply additional benefit on long time MACCE as compared with culprit-only intervention strategy in patients presenting with AMI for urgent PCI with multivessel disease.